2013
DOI: 10.1210/en.2013-1227
|View full text |Cite
|
Sign up to set email alerts
|

Elevated Mechanical Loading When Young Provides Lifelong Benefits to Cortical Bone Properties in Female Rats Independent of a Surgically Induced Menopause

Abstract: Exercise that mechanically loads the skeleton is advocated when young to enhance lifelong bone health. Whether the skeletal benefits of elevated loading when young persist into adulthood and after menopause are important questions. This study investigated the influence of a surgically induced menopause in female Sprague-Dawley rats on the lifelong maintenance of the cortical bone benefits of skeletal loading when young. Animals had their right forearm extrinsically loaded 3 d/wk between 4 and 10 weeks of age u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 43 publications
1
14
1
Order By: Relevance
“…Based on this evidence, the level of PA needed to maintain bone size and strength benefits, obtained by a physically active lifestyle in adolescence, is likely less than the activity needed for structural adaptation. Previous observations from retired athletes and animal experiments support this concept. Experimental studies have indicated lifelong benefits in cortical bone from loading stimulus obtained during skeletal growth .…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…Based on this evidence, the level of PA needed to maintain bone size and strength benefits, obtained by a physically active lifestyle in adolescence, is likely less than the activity needed for structural adaptation. Previous observations from retired athletes and animal experiments support this concept. Experimental studies have indicated lifelong benefits in cortical bone from loading stimulus obtained during skeletal growth .…”
Section: Discussionmentioning
confidence: 73%
“…Previous observations from retired athletes and animal experiments support this concept. Experimental studies have indicated lifelong benefits in cortical bone from loading stimulus obtained during skeletal growth . Altogether, this evidence suggests that developing larger cortex during growth may provide lifelong antifracture benefits by priming the skeleton to offset the cortical bone thinning and trabecularization of the endocortical bone associated with aging .…”
Section: Discussionmentioning
confidence: 73%
“…All tests here took place in fluid. In other studies using this technique to quantify collagen nanoscale morphology, shifts in the D-spacing distribution have been noted following estrogen deficiency (Wallace et al 2010b; Warden et al 2013) and with Osteogenesis Imperfecta (Wallace et al 2011; Kemp et al 2012) in multiple tissues, but not between different tissue types in healthy mice (Wallace et al 2010a), or between male and female mice. This study demonstrated that diabetic tendons had a distribution of fibril D-spacings that was narrower versus control (Figure 2).…”
Section: Discussionmentioning
confidence: 99%
“…Although postulated to have a singular value of 67 nm (Hodge and Petruska 1963), recent work has shown that D-spacing exists with a distribution of values (Wallace et al 2010a). This distribution changes with several disease states in bone (Wallace et al 2010a; Wallace et al 2011; Warden et al 2013), skin (Fang et al 2012) and tendon (Kemp et al 2012), suggesting a metric that may represent a diagnostic option for diseases in collagen-based tissues. To put functional meaning behind this measure of nanoscale morphology, recent work focused on mechanically probing collagen fibrils (Kemp et al 2012; Wallace et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Beneficial effects of the early introduction of exercise regimens in growing horses are well documented [98][99][100]. Bone is most adaptable prior to maturity, and the benefits of early adaptation are long lasting [101][102][103].…”
Section: Risk Factors Associated With Bone Fatigue Failure Agementioning
confidence: 99%